A 28-kDa Glycoprotein Functions as a Platelet Ligand for P-selectin (CD62P) - Li, Ling; Qian, Kai-Xian; Geng, Jian-Guo (Thrombosis and Haemostasis, 2002)
P-selectin (CD62P) is expressed on activated platelets and on stimulated endothelial cells. It interacts with P-selectin glycoprotein ligand-1 (PSGL-1; CD162) for adhesion of activated platelets on leukocytes and for rolling of leukocytes on stimulated endothelial cells. Recently, resting and activated platelets have been shown to roll on endothelial P-selectin, indicating that platelets express (a) ligand(s) for P-selectin. Here we show that P-selectin specifically precipitated one 28-kDa glycoprotein from the whole cell lysates and the membrane lysates of human platelets in a Ca2+-dependent manner. Further, the purified 28-kDa molecule could inhibit the binding of P-selectin to human resting and activated platelets. In contrast, KPL1 (a leukocyte adhesion blocking MoAb to PSGL-1) did not neutralize the binding of P-selectin to human platelets, even though it abolished the binding of P-selectin to human promyeloid HL-60 cells. Our results thus indicate that the 28-kDa glycoprotein may function as an important platelet ligand for P-selectin.
Keywords: Platelets; P-selectin (CD62P); thrombosis; glycoprotein; ligand